SLUM TOURISM: INDONESIAN TOURISM PROMOTION AND DEVELOPMENT STRATEGY (PROBLEM OR SOLUTION) - Wijaya, Verina; Mitasari, Rean; Kusumawijaya, Erris; Adityaji, Rizki; Widyawati, Christy (JURNAL ILMIAH EDUNOMIKA, 2024)
Basically, the concept of tourism development and promotion using the Slum Tourism/Poverty Tourism concept is good for projection in tourism development and promotion because tourists directly interact with local communities, increase their sense of human dignity, and offer new ideas to create new ideas. However, this concept has clashes that are not in line with the concept of Indonesian tourism branding, namely "Pesona Indonesia" which shows the natural beauty and beauty of Indonesia. Therefore, this research aims to analyze the concept of Slum Tourism in developing and promoting Indonesian tourism as a solution or problem. The data used in this research is secondary data using library research data collection techniques. The data collected was analyzed using the smart PLS 3.0 method. Keywords: Slum Tourism, Promotion, Development, Problem, Solution